Digital Finance in Europe: Law, Regulation, and Governance - Avgouleas, Emilios; Marjosola, Heikki (European Company And Financial Law Review - Special Volume, 2021)
This special volume collects contributions from leading scholars who scrutinize the challenges digital finance presents for the EU internal market and financial market regulation from multiple public policy perspectives. Author contributions aim to provide policy-relevant research and ideas shedding light on the complexities of the digital finance promise. They also offer solid proposals for reform of EU financial services law.